2021
DOI: 10.3389/fonc.2021.775079
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Scoring System for Early Diagnosis of Malignant Pleural Effusion Based on a Nomogram

Abstract: BackgroundThe diagnostic value of clinical and laboratory features to differentiate between malignant pleural effusion (MPE) and benign pleural effusion (BPE) has not yet been established.ObjectivesThe present study aimed to develop and validate the diagnostic accuracy of a scoring system based on a nomogram to distinguish MPE from BPE.MethodsA total of 1,239 eligible patients with PE were recruited in this study and randomly divided into a training set and an internal validation set at a ratio of 7:3. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(66 reference statements)
0
8
0
1
Order By: Relevance
“…Nomograms are a graphical representation of a complex mathematical formula, which are widely used to estimate diagnosis and prognosis for a variety of diseases by integrating clinical, biologic, and/or genetic variables in medicine [22]. Previously, we and other investigators had reported the application of nomogram in differentiating MPE from BPE [23,24]. In the present study, we developed a scoring system based on a nomogram to distinguish TPE from non-TB BPE.…”
Section: Discussionmentioning
confidence: 98%
“…Nomograms are a graphical representation of a complex mathematical formula, which are widely used to estimate diagnosis and prognosis for a variety of diseases by integrating clinical, biologic, and/or genetic variables in medicine [22]. Previously, we and other investigators had reported the application of nomogram in differentiating MPE from BPE [23,24]. In the present study, we developed a scoring system based on a nomogram to distinguish TPE from non-TB BPE.…”
Section: Discussionmentioning
confidence: 98%
“… 6 – 11 Therefore, scholars pay more attention to build prediction models that combine at least two blood or PE indicators with the advantages of less invasion, cheaper, easy acquirement, and simpler based on current reliable medical diagnosis resources. 12 15 , 17 21 …”
Section: Discussionmentioning
confidence: 99%
“…The reported good sensitivity, specificity, and area under the curve (AUC) of these prediction models to distinguish MPE from BPE were about 85–89%, 82–92%, and 91–98%, respectively, which showed greatly improved diagnostic efficiency of MPE. 12 15 However, these clinical prediction models contain at least six markers and they are not simple enough to be widely used in heavy clinical work.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity, specificity, PPV, and PLR were 67.7%, 91.0%, 61.5%, and 9.55, respectively. Previously, we also developed and validated a scoring system based on a nomogram for distinguishing MPE and BPE, which performed well for differentiating lung cancer and tuberculosis [ 31 ]. However, the diagnosis of MPE was according to the presence of malignant cells in PE cytology in our previous study [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we also developed and validated a scoring system based on a nomogram for distinguishing MPE and BPE, which performed well for differentiating lung cancer and tuberculosis [ 31 ]. However, the diagnosis of MPE was according to the presence of malignant cells in PE cytology in our previous study [ 31 ]. At present, many clinicians still regard positive cytology as the gold standard for MPE diagnosis, but the accuracy rate of this method is only about 60% [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%